Dividend Initiation Policy and the Effect on Dividend Sustainability (At Initial Public Offering Companies on the Indonesia Stock Exchange) - Hitten, Akhmad; Mustaruddin, Mustaruddin; Rustam, M. (International Journal of Economics and Financial Issues, 2019)
This study aims to examine the effects of maturity and agency cost model variables on the behavior of dividend initiation policy, and the effect itself on dividend sustainable. Samples of 93 non-financial companies that have Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX), 2005 - 2017. This study uses Structural Equation Modeling with SmartPLS software to test the hypothesis. The test results show: maturity and capital structure variable have significant and positive effects on dividend initiation policy. Ownership structure does not affect the dividend initiation policy. Dividend initiation variable has a significant and positive effect on dividend sustainable. Keywords: Agency Cost Model; Dividend Initiation Policy; Dividend Sustainability. JEL Classification: F12, F30, F39 DOI: https://doi.org/10.32479/ijefi.8469